Folate Receptor Alpha Is Preferentially Expressed in the Carcinoma Component of Endometrial Carcinosarcomas: A Potential Target for Adjuvant Therapy. (14th September 2021) - Hanley, Krisztina Z.; Horowitz, Ira R.; Gordon, Alan; Meisel, Jane; Khanna, Namita
Abstract : Carcinosarcomas (CSs) of the endometrium are biphasic malignancies, composed of high-grade carcinomatous and sarcomatous components. Surgical stage and pathologic characteristics are the most important prognostic findings, with a 5-yr survival of 15% to 30% in advance stage disease. Folate receptor alpha (FRA) overexpression has been observed in endometrial carcinomas and not yet studied in CSs. This study evaluates semiquantitative expression of FRA in both carcinomatous and sarcomatous components of CSs on whole tissue sections. Immunohistochemistry for FRA expression was performed and extent and intensity of staining were recorded for each case for both histologic components. A total of 46 cases were stained for FRA. The majority of these (40/46, 87%) showed FRA staining at variable intensity in the carcinomatous component, stronger in serous carcinomas and high-grade endometrioid, while only a small subset of tumors demonstrated weak staining in the sarcomatous component (2/46, 4.35%). CS is known to be associated with poor prognosis and adjuvant therapy is recommended even in low stage disease. Serous and high-grade endometrioid carcinomas are the most common carcinomatous components of CSs and are known to show consistently high FRA expression. Folate plays a role in tumor cell migration and loss of cellular adhesion, which are key steps in epithelial-mesenchymal transition, the process by which CS develops from carcinoma cells. Our study shows expression of FRA in the carcinomatous component of almost all CS cases (87%), further favoring FRA as a target for adjuvant treatment. While expression of FRA in the sarcomatous component was rarely observed, the carcinomatous component being associated with metastatic potential underscores the importance of anti-FRA therapy for systemic disease control.